2019
DOI: 10.1177/0269094219889603
|View full text |Cite
|
Sign up to set email alerts
|

Examining the power role of Local Authorities in planning for socio-economic event impacts

Abstract: The socio-economic impacts of events, while mostly positive can often bring many detrimental implications to destinations and communities that host them. The statutory role of Local Authorities in Ireland to authorise and license large scale outdoor public events places Local Authorities in an ideal position to monitor and better manage the socio-economic impacts events can create at local level. This comparative examination draws attention to the current level of planning for the socio-economic impacts of eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Although convenient, as a moniker "events officers" masks a range of institutional arrangements and professional roles among those participating in the research, an observation consistent with previous research (Thomas and Wood, 2004;Wood, 2005). This is not unique to the UK (Maguire, 2019(Maguire, , 2021 and, as the interviews for this study confirmed (see below), not all participants were exclusively or directly employed by local authorities. Some were employed outside the council apparatus, for instance in community interest companies or private limited companies established by local authorities to manage and service events (and frequently other) functions, with the municipality usually as the principal stakeholder and investor.…”
Section: Methodssupporting
confidence: 82%
See 3 more Smart Citations
“…Although convenient, as a moniker "events officers" masks a range of institutional arrangements and professional roles among those participating in the research, an observation consistent with previous research (Thomas and Wood, 2004;Wood, 2005). This is not unique to the UK (Maguire, 2019(Maguire, , 2021 and, as the interviews for this study confirmed (see below), not all participants were exclusively or directly employed by local authorities. Some were employed outside the council apparatus, for instance in community interest companies or private limited companies established by local authorities to manage and service events (and frequently other) functions, with the municipality usually as the principal stakeholder and investor.…”
Section: Methodssupporting
confidence: 82%
“…In fact, local authorities have long been identified as major stakeholders in organising and operating events (Thomas and Wood, 2004 ; Wood, 2005 ; Maguire, 2019 , 2021 ), and they play pivotal roles in co-ordinating responses to crises and catastrophes in visitor economies (Ritchie, 2009 ). For municipalities, participation in event planning, management or regulation can deliver a range of outcomes, not least economic benefits (Wood, 2005 ; Maguire, 2019 ). They may also be conceptualised as delivering a public good and justified on the basis of non-market benefits, including enriching local social and cultural life.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Much scholarship, when addressing sustainability, considers environmental impacts and management [17,18]. Economic sustainability is ever-pressing, especially as competition to attract tourists, consumers and new clientele bases is increasing and thus destinations need to host events or display tourism products that are up-to-date and meet current demands [19,20]. However, there is increased emphasis on social and community impacts, perhaps as these are intangible impacts that relate to local attitudes about places as well as quality of life for residents and businesses in destinations [21][22][23][24][25], especially as places continually change and transform-which then calls for new forms of participation [26,27] and ways of evaluating social impacts [28].…”
Section: Overview Of the Special Issue Themementioning
confidence: 99%